Adding value to imperfect long-term animal monitoring data for conservation insight - S.D. Sarre; E.J. Stringer; R. Brawata; E. Carlson; R. Colley; E. Cook; B. Croak; L.I. Doucette; M. Hoehn; B. Howland; W.S. Osborne; S. Pulsford; et al. (Biological Conservation, 2026)

Bourbon Barrels and Bottlenecks: a Nuanced Look at Thirty Years of White Oak Population Dynamics - Lance A. Vickers; Benjamin O. Knapp; Thomas Goff; Thomas J. Brandeis; John M. Lhotka; Randall S. Morin; Kenton L. Sena; Jeffrey W. Stringer (Journal of Forestry, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

A Review of Translational Magnetic Resonance Imaging in Human and Rodent Experimental Models of Small Vessel Disease - Michael S. Stringer; Hedok Lee; Mikko T. Huuskonen; Bradley J. MacIntosh; Rosalind Brown; Axel Montagne; Sarah Atwi; Joel Ramirez; Maurits A. Jansen; Ian Marshall; Sandra E. Black; Berislav V. Zlokovic; et al. (Translational Stroke Research, 2021)
Cerebral small vessel disease (SVD) is a major health burden, yet the pathophysiology remains poorly understood with no effective treatment. Since much of SVD develops silently and insidiously, non-invasive neuroimaging such as MRI is fundamental to detecting and understanding SVD in humans. Several relevant SVD rodent models are established for which MRI can monitor in vivo changes over time prior to histological examination. Here, we critically review the MRI methods pertaining to salient rodent models and evaluate synergies with human SVD MRI methods. We found few relevant publications, but argue there is considerable scope for greater use of MRI in rodent models, and opportunities for harmonisation of the rodent-human methods to increase the translational potential of models to understand SVD in humans. We summarise current MR techniques used in SVD research, provide recommendations and examples and highlight practicalities for use of MRI SVD imaging protocols in pre-selected, relevant rodent models.

Investigating the use of Paleolithic perforated batons: new evidence from Gough’s Cave (Somerset, UK) - C. Lucas; J. Galway-Witham; C. B. Stringer; S. M. Bello (Archaeological and Anthropological Sciences, 2019)

Extracellular Vesicles Released by Glioblastoma Cells Stimulate Normal Astrocytes to Acquire a Tumor-Supportive Phenotype Via p53 and MYC Signaling Pathways - S. Hallal; D. M. Mallawaaratchy; H. Wei; S. Ebrahimkhani; B. W. Stringer; B. W. Day; A. W. Boyd; G. J. Guillemin; M. E. Buckland; Kimberley L. Kaufman (Molecular Neurobiology, 2019)

The biodiversity of the United Kingdom’s Overseas Territories: a stock take of species occurrence and assessment of key knowledge gaps - Thomas Churchyard; M. A. Eaton; S. Havery; J. Hall; J. Millett; A. Farr; R. J. Cuthbert; C. Stringer; J. A. Vickery (Biodiversity and Conservation, 2016)

Participatory Evaluation of Monitoring and Modeling of Sustainable Land Management Technologies in Areas Prone to Land Degradation - L. C. Stringer; L. Fleskens; M. S. Reed; J. de Vente; M. Zengin (Environmental Management, 2014)

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Continuous transformation learning of translation invariant representations - G. Perry; E. T. Rolls; S. M. Stringer (Experimental Brain Research, 2010)

Path integration of head direction: updating a packet of neural activity at the correct speed using neuronal time constants - D. M. Walters; S. M. Stringer (Biological Cybernetics, 2010)

Learning invariant object recognition in the visual system with continuous transformations - S. M. Stringer; G. Perry; E. T. Rolls; J. H. Proske (Biological Cybernetics, 2006)

Feasibility of Tissue Plasminogen Activator Formulated for Pulmonary Delivery - John S. Dunn; Rajiv Nayar; Jackie Campos; Brooks M. Hybertson; Yue Zhou; Mark Cornell Manning; John E. Repine; Kathleen A. Stringer (Pharmaceutical Research, 2005)

Comparison of partial sequence of the cap binding protein (eIF4E) isolated from Agaricus bisporus and its pathogen Verticillium fungicola - A.L. Athey-Pollard; M. Kirby; S. Potter; C. Stringer; P.R. Mills; G.D. Foster (Mycopathologia, 2003)

Invariant recognition of feature combinations in the visual system - M. C. M. Elliffe; E. T. Rolls; S. M. Stringer (Biological Cybernetics, 2002)

Quarantine and regulatory issues pertaining to use of ca and/or fumigation - A. Carpenter; C. W. van Epenhuijsen; I. A. N. Stringer; Y. L. Ren; J. M. Desmarchelier; Judith Downey; G. Eddy; H. J. Banks; J: van S. Graver (Phytoparasitica, 2001)